What Do They Do with Their Phones? Teens' Smartphone Use Behavior Post Covid-19 Pandemic - Dewi Ilma Antawati; Rinanti Resmadewi; Dafa Revrison Muttaqien (Journal of Educational, Health and Community Psychology, 2024)
The use of smartphones has significantly increased during the Covid-19 pandemic. Internet access in the family room has impacted teens' smartphone usage behavior and relationships between family members, particularly in family communication. This study aimed to describe teens' behavior while using smartphones and compare the quality of parent-child interpersonal communication based on teens' smartphone usage intensity post-pandemic COVID-19. A total of 515 teens aged 15-19 years participated in this research. The study revealed eight main activities that most teenagers engage in with their smartphones. These activities include recording pictures/audio/video of oneself, managing incoming messages (via messaging apps and email), playing games, accessing social media, listening to music, listening to the radio, editing photos/videos, and using search engines (such as Google) to search for information (browsing). The results also indicated significant differences in openness, empathy, positiveness, and overall family communication quality. Participants who used low-intensity gadgets exhibited the best quality in these dimensions. The implications of this research may help practitioners working with families design necessary interventions for family communication problems.